2005
DOI: 10.1038/sj.jcbfm.9600004
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Activation of NF-κB Contributes to Cell Death in Cerebral Ischemia

Abstract: The transcription factor NF-kappaB is a key regulator of inflammation and cell survival. NF-kappaB is activated by cerebral ischemia in neurons and glia, but its function is controversial. To inhibit NF-kappaB selectively in neurons and glial cells, we have generated transgenic mice that express the IkappaBalpha superrepressor (IkappaBalpha mutated at serine-32 and serine-36, IkappaBalpha-SR) under transcriptional control of the neuron-specific enolase (NSE) and the glial fibrillary acidic protein (GFAP) promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
165
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 201 publications
(174 citation statements)
references
References 58 publications
9
165
0
Order By: Relevance
“…Likewise, functional parameters of visual acuity and contrast sensitivity were indistinguishable between WT and RelA CNSKO mice (published elsewhere). These findings are in line with previous reports showing that mice with inactivated upstream regulators of NF-kB (IkBa, IKK) in the neuro-glial compartment are indiscernible regarding overall neuro-anatomical and behavioral features 3,4 and, in particular, display normal myelination. 5 Among the NF-kB family members (RelA, RelB, c-Rel, p105/50, p100/52), only deletion of the subunit p50, which lacks a transcriptional activator domain, results in a destructive neuronal phenotype as characterized by precocious aging, neuronal apoptosis and spontaneous demyelination in young adult mice.…”
supporting
confidence: 93%
“…Likewise, functional parameters of visual acuity and contrast sensitivity were indistinguishable between WT and RelA CNSKO mice (published elsewhere). These findings are in line with previous reports showing that mice with inactivated upstream regulators of NF-kB (IkBa, IKK) in the neuro-glial compartment are indiscernible regarding overall neuro-anatomical and behavioral features 3,4 and, in particular, display normal myelination. 5 Among the NF-kB family members (RelA, RelB, c-Rel, p105/50, p100/52), only deletion of the subunit p50, which lacks a transcriptional activator domain, results in a destructive neuronal phenotype as characterized by precocious aging, neuronal apoptosis and spontaneous demyelination in young adult mice.…”
supporting
confidence: 93%
“…In addition, ERs are known to inhibit the transcription factor nuclear factor-kB (Biswas et al, 2005), an effect that has also been reported in a model of cerebral ischemia in vivo (Wen et al, 2004). Inhibition of nuclear factor-kB in neurons is protective in stroke models Zhang et al, 2005), suggesting that pathwayselective ER ligands that inhibit nuclear factor-kB (Chadwick et al, 2005) might be an option for stroke treatment. Another way to refine estrogen treatment for stroke therapy would be the development of neuron-specific selective ER modulators (neuroSERMs) (Zhao et al, 2005), a strategy that would exploit the important role of neuronal ERa shown in this study.…”
Section: Discussionmentioning
confidence: 80%
“…Evidence for NF-kB activation has also been reported in important examples of neurodegeneration, such as Alzheimer's disease (Kaltschmidt et al, 1997;Akama et al, 1998) and Parkinson's disease (Hunot et al, 1997). Zhang et al (2005) recently observed that neuronal activation of NF-kB in cerebral ischemia contributed to ischemic brain damage in vivo. A dual action for NF-kB has been proposed in hippocampal neurons in a global ischemia model, whereby it might be either protective or detrimental depending on the onset and duration of its activation (Clemens et al, 1998).…”
Section: Discussionmentioning
confidence: 99%